Menggali Akar Rasisme: Analisis Terhadap Pembentukan Stigma dan Dampaknya Pada Masyarakat - Azmarni Zulfa; Putri Ayu Lestari; Prespi Julihasti; Adinda Desma Andini; Zulfadha Khairunnisa; Rahmi Amanda; Irmayanti Arfah (Jurnal Manajemen dan Pendidikan Agama Islam, 2024)
This research delves into the formation of racial stigma and its impact on society, exploring the factors contributing to the emergence of discriminatory attitudes. Utilizing a qualitative descriptive method with a literature review approach, the study investigates historical, cultural, and institutional elements shaping racial perceptions. The analysis not only scrutinizes "how" racial stigma forms but delves into the "why" of discriminatory attitudes, encompassing historical, policy, and social norm influences. The research findings aim to contribute significantly to understanding the intricate interplay between racial stigma and its societal repercussions, identifying patterns that may be challenging to detect without a holistic overview.